Pengaruh Model Problem Based Learning Berbantuan E-LKPD Interaktif Terhadap Kemampuan Pemecahan Masalah Matematika Siswa Kelas VIII SMP Negeri 11 Mataram Tahun Ajaran 2025/2026 - Kayanti, Kusamantha Dwi; Turmuzi , Muhammad; Kurniati, Nani (Griya Journal of Mathematics Education and Application, 2025)
The background of this study is the low problem-solving ability of students due to the use of ineffective learning models and the minimal use of learning media. This study aims to determine the effect of the E-LKPD Interactive-assisted Problem-Based Learning (PBL) model on the mathematical problem-solving ability of eighth-grade students at SMP Negeri 11 Mataram in the 2025/2026 academic year. The type of research used is a quasi-experimental design with a quantitative approach. The population in this study consisted of 96 eighth-grade students with a sample of 48 students selected using cluster random sampling. Data collection techniques were carried out through observation and tests. Data were obtained through posttests and analyzed using the t-test. The results of the analysis showed that the t-count = 2.806 was greater than the t-table = 2.013, so was accepted and was rejected. Thus, there was a significant difference in mathematical problem-solving skill between the experimental class and the control class. The effect size value of indicates that the effect is in the strong category.